TERATOGENIC EFFECTS OF LEAD ACETATE ON KIDNEY - Jabeen, R; Tahir, M; Waqas, S (Journal of Ayub Medical College Abbottabad, 2010)
Background: Lead remains a considerable occupational and public health problem, which is known to cause a number of adverse effects in both men and women. Conflicting reports have appeared on lead induced nephrotoxicity in experimental studies in the past. There is hardly any work on its teratogenic effects on kidney. Present study was therefore designed to investigate the effects of lead acetate on developing kidney. Methods: Twelve mice were used as experimental model and were divided into two groups of six animals each; group A served as control group and B was used as an experimental group. Lead acetate (10 mg/kg) dissolved in 0.02 ml of distilled water was administered as a single daily dose orally to group B whereas weight related amount of distilled water was given to group A for the entire period of experiment. On 18th day of gestation foetuses were dissected free of uterine wall under the dissecting microscope and were sacrificed; kidneys were removed and fixed in 10% formalin, dehydrated in ascending grades of alcohol, cleared in xylene and infiltrated with filtered paraffin. The paraffin blocks were made and five micron thin sections were obtained using a rotary microtome. The sections were stained with Hematoxylin and eosin and, PAS; these were examined under light microscope. Results: Significant decrease in cortical thickness was observed which varied from 578.6±1.4 µm in group A to 515.6±5 µm in group B (p<0.001). Diameter of renal corpuscles varied from 57.7±0.07 µm in group A to 50.5±0.07 µm in group B (p<0.001). Moderate cortical tubular atrophy showing thickening of endothelial basement membrane in glomeruli, desquamated epithelium with degenerated nuclei in proximal and distal tubules were observed in group B in contrast to group A. Conclusion: The results of the investigation indicated that lead acetate administration to the dams produced deleterious effects on the developing kidney in mice. Keywords: Lead acetate, nephrotoxicity